Social Investment Programme and Livelihood of the Vulnerable: A Focus on Nigeria Post COVID-19 Pandemic - Onuoha, Onyekachi Chibueze; Okafor, Nnamdi Ikemefuna (Rescollacom (Research Collaborations Community), 2023)
Introduction: In an effort curb the effect and the spread of the COVID-19 pandemic, several countries’ governments took firm decisions and actions to ensure that the pandemic was contained before vaccines were developed including the closure of sea, land, and airport borders, banning all gatherings, closure of schools, and all forms of gathering, social distancing as well as locking down their economies to restrict vehicular and human movement. Nigeria was one of the most affected African countries, the Government therefore adopted strategies to minimize the effect of the lockdown on the citizens which included the distribution of relief materials and the re-engineering of its social investment programme that was earlier established in 2016, targeting the vulnerable people including the youths, children, and women. However, lack of transparency, and accountability of the funds by the assigned government personnel have been highly reported. Therefore, this research aimed at carrying out an in-depth investigation and evaluation of the social investment programmes on the livelihood of the vulnerable in Nigeria.Methodology: The descriptive survey method was adopted as the research design for the study. The primary data from strategic community leaders who are privy to information on all financial and material support provided to any member of their communities were generated. Seventy-nine (79) communities were studied across all six geopolitical zones in the country using a structured questionnaire. The data generated were analysed using simple percentages, mean, and standard deviation.Results: The results for N-power programme, conditional cash transfer (CCT) programme, government enterprise and empowerment programme (GEEP), the home-grown-school feeding programme (HGFP) were established. The obtained results in general demonstrated a low and a moderate impact or effect of the government social programmes on the livelihood of the targeted Nigerians (vulnerable). This was evident enough across all the results discussed below with a low mean value which is a clear indication of the misappropriation, little or no transparency, dishonesty and corruption involved by the assigned government agencies or officials to carry out these tasks.